Pengendalian Data Pribadi Dan Ruang Siber Oleh Platform Digital Big Data Global Terkait Kedaulatan Digital Indonesia - Yokotani, Yokotani; Kurnia, A. Cery; Wirazilmustaan, Wirazilmustaan; Salfutra, Reko Dwi (Fakultas Hukum Universitas Bangka Belitung, 2025)
The development of global digital technology has brought significant challenges to Indonesia's digital sovereignty, especially regarding the control of personal data and cyberspace. Foreign digital platforms that dominate use in Indonesia process citizens' data massively through big data mechanisms, often outside the jurisdiction of national law. This dependence poses risks to personal data protection, national security, and state control over digital infrastructure. This study uses normative legal methods with a legislative and conceptual approach to examine the role of national regulations, such as Law Number 27 of 2022 concerning Personal Data Protection, in strengthening the state's position. The results of the study show that strengthening regulations, developing local technology, community digital literacy, and international cooperation are key strategies to uphold Indonesia's digital sovereignty. Without concrete and comprehensive steps, control over data and digital space will continue to be in the hands of foreign entities, which can weaken the nation's independence in the digital era.